Master class : lessons from leading writers - Bunge, Nancy L. (University of Iowa Press, 2005)
Master Class: Lessons from Leading Writers gathers more than two decades of wisdom from twenty-nine accomplished authors. It offers previously unpublished interviews along with freshly edited versions of ten interviews from Nancy Bunge's well-received previous collection, Finding the Words. The first section, Theory, incorporates interviews which document the golden age of writing programs in which authors with a strong sense of social and cultural responsibility taught as seriously as they wrote. These conversations delve into the writers' philosophies and teaching methods. The second section.